Supporting decisions on conflicting land-uses: An integrated ecological-economic approach - Bernd Klauer; Frank Messner; Felix Herzog (UFZ-Umweltforschungszentrum Leipzig-Halle, 1999)
An integrated ecological-economic decision-making approach is developed to help local stakeholders decide on land use in rural areas where the conflict between natural resource protection and economic development is pressing. It consists of four methodological steps. In the first step the political options and alternatives for action regarding changes in the land-use pattern are specified in order to derive politically relevant land-use strategies (scenarios). In the second step economic, ecological and social indicators are derived. The third step includes economic modelling (economic input-output model), environmental modelling (modelling of landscape water balance) and the qualitative and quantitative estimation of ecological and environmental effects. These efforts result in the production of a multi-indicator matrix. Finally, the fourth step deals with a combined monetary and multi-criteria evaluation resulting in a ranking of the land-use strategies. The discussion of the decision-making approach concentrates on the necessity of preliminary decisions and the possibility and necessity of stakeholders participation in the decisionmaking process.
Keywords: 330; evaluation; decision-making; multi-criteria analysis; land-use management; scenarios; benefit-cost analysis